Effects of Mixed Mineral Supplementation in On-Farm Feeds on the Metamorphosis Development and Growth Performances of Frog (Hoplobatrachus rugulosus) Tadpoles - Boonta, Teppitag; Whangchai, Niwooti; Chitmanat, Chanagun; Pimpimol, Tipsukhon; Gutierrez, Redel L.; Tongsiri, Sudaporn (Journal of Fisheries and Environment, 2024)
The frog (Hoplobatrachus rugulosus) is widely cultured in Asian countries. Tadepoles in these cultures are prone to diseases and sensitive to environmental factors, but their metamorphosis and growth may be enhanced by applying minerals. Therefore, this study was conducted to determine the influence of mixed mineral supplementation in on-farm feeds on the metamorphosis development, growth performance, and production cost of H. rugulosus tadpoles. Four levels of mixed mineral supplementation (0%, 0.2%, 0.4%, and 0.6%) were fed to groups of 500 tadpoles stocked in cement ponds. Tadpoles were fed experimental feeds at 5% of their body weight for 35 days. The 0.2% supplementation group showed significantly greater average weight gain (3.84±0.15 g·tadpole-1) and survival rate (81.00±0.47%) compared to the 0.6% and 0% groups (p<0.05), but was comparable (p>0.05) to the 0.4% group. Notably, other growth parameters (average daily weight gain, specific growth rate, and feed conversion ratio) did not differ significantly (p>0.05) among treatments. The groups receiving mineral supplementation showed significantly (p<0.05) higher average forelimb length than the control from day 20 until day 28, but not from days 30 to 36. Conversely, mineral supplementation did not affect hindlimb length throughout the experiment. Tadpoles receiving 0.2% supplementation completed metamorphosis faster than other groups, starting on day 26 and reaching 100% completion by day 34. This study demonstrated that feeding 0.2% mixed mineral supplementation to frog tadpoles accelerated the metamorphosis and improved their growth, albeit with a slight increase in production costs.